The interplay of bosentan and finerenone in amelioration of cardiac dysfunction within benign prostatic hyperplasia in rats - Marwa Monier Mahmoud Refaie; Asmaa A. Hasan; Asmaa A. Muhammed; Randa Ahmed Ibrahim; Eman Abdel Naby Hassan; Enas Fathy; Aml Mohamed Soliman; Hoda S. Sherkawy; Olivia N. Beshay; Amr Alam-Eldin Ahmed; Ahmed Ahmed; Samar Hisham Elsayed; et al. (Molecular Biology Reports, 2026)

Multifunctional bioactivities of Phyllanthus emblica L. fruit extracts: linking phytochemical profiling to antileishmanial, antioxidant and antibacterial effects in vitro and in vivo - Zeyad Taha Hussein; Samar Derbali; Omaima Ibrahim Mahmood; Mohamed Trigui (Euro-Mediterranean Journal for Environmental Integration, 2026)

Bioactivity of cress and cypress emulsifiable concentrate plant oils against Spodoptera littoralis: toxicity, nutritional disruption, and in silico binding studies - Samar S. Ibrahim; Hala M. Metwally (Journal of Plant Diseases and Protection, 2026)

Fermentation Status Dictates Organ-Selective Protection of a Millet-Based Dairy Beverage Against Sub-Chronic Lead Toxicity in Rats - Amel A. Ibrahim; Hala A. Hafez; Samar M. Aborhyem; Reham A. Madian; Noha Dyab (Biological Trace Element Research, 2026)

Correction to: Repurposing doxycycline as an adjunct to sitagliptin in type 2 diabetes mellitus: a randomized controlled study on glycemic, inflammatory, and cardiometabolic outcomes - Eman El‐Khateeb; Mohannad O. Khrieba; Amal Mohammad Badawoud; Ahmed A. Morsy; Aya A. El‑Hanafy; Eman Hamza; Eslam Habba; Doaa A. El‑Hanafy; Nashwa Eltantawy; Reham A. Al‑Dhelaan; Kholoud H. Radwan; Abeer A. El‑Sayed; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Modulation of the ACLY–AMPK axis by bempedoic acid suppresses NF-κB-driven inflammation, VEGF–Notch angiogenic crosstalk, and cell-cycle progression in Solid Ehrlich Carcinoma - Asmaa Saleh; Nahed A. Raslan; Heba Mohammed Refat M. Selim; Ahmed Mohamed Farghly; Sahar K. Ali; Omneya Galal; Bassant M. Barakat; Reda M. Fayyad; Samar H. Rizk; Shaza M. Elhusseiny; Amina Ibrahim Badawy; Huda Mahmoud Fettouh Saadat; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Bacillus biocontrol agents suppress wheat powdery mildew and are associated with structural alterations observed by scanning electron microscopy - Samar M. Esmail; Motrih Al-Mutiry; Ibrahim S. Draz; Naglaa A. Taha; Wael F. Shehata; Najat Marraiki; Ola I. Mabrouk; Heba I. Saad-El-Din; Osama E. Abd El Badeea; Said M. Kamel; Mohamed Abou-Zeid (Physiological and Molecular Plant Pathology, 2026)

Exploring the therapeutic potential of Lupeol isolated from Ochrosia elliptica Labill. leaves in polycystic ovarian syndrome - Essam Abdel-Sattar; Marwa A. Ibrahim; Fady Sayed Youssef; Marwa S. Khattab; Riham A. El-Shiekh; Rehab A. Ghandour; Shimaa R. Emam; Heba Hozyen; Marwa Zakaria; Samar M. Mouneir (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Repurposing doxycycline as an adjunct to sitagliptin in type 2 diabetes mellitus: a randomized controlled study on glycemic, inflammatory, and cardiometabolic outcomes - Eman El‐Khateeb; Mohannad O. Khrieba; Amal Mohammad Badawoud; Ahmed A. Morsy; Aya A. El-Hanafy; Eman Hamza; Eslam Habba; Doaa A. El-Hanafy; Nashwa Eltantawy; Reham A. Al-Dhelaan; Kholoud H. Radwan; Abeer A. El-Sayed; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Genomic Approaches: an Effective Approach to Determine the Biosynthetic Genes in Actinobacteria - Abrar Ahmed AbuHamdia; Dina Hatem Riad; Samar Ibrahim Shaheen; Wafaa Stohy Yusuf (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2026)

The role of mitochondrial dysfunction, oxidative stress, and gender in cardiac fibrosis and vascular remodeling in an induced aged rat model with possible mitigation by eugenol nano-emulsion - Rawan H. Hanafi; Marwa S. Khattab; Sara M. Baraka; Saber Ibrahim; Samar H. Elsharkawy; Reda M. S. Korany (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Cardiac diseases are strongly associated with aging and pose a major threat to survival. This study evaluated the cardioprotective effects of oral eugenol and its nano-emulsion (20 mg/kg) in a D-galactose-induced aging model (300 mg/kg, i.p.) in male and female rats over 12 weeks. Particle size and zeta potential analyses confirmed the successful development of a stable, well-dispersed nano-emulsion system. At the end of treatment, echocardiography, biochemical assays, histopathology, and immunohistochemistry were performed. Cardiac dysfunction and dilatation were more pronounced in males than females following D-galactose administration, as evidenced by left ventricular internal diameter in diastole (LVIDd) and left ventricular internal diameter in systole (LVIDs), and reduced ejection fraction (EF) and fractional shortening (FS). Both eugenol and its nano-emulsion preserved cardiac architecture and mitigated histopathological alterations, including myofibrillar distortion, necrosis, vascular remodeling, and fibrosis. Treatment significantly reduced oxidative stress and mitochondrial dysfunction by restoring GSH, lowering MDA, and modulating the PINK1/Mfn2 pathway. Furthermore, eugenol and its nano-emulsion attenuated cardiac inflammation, apoptosis, and fibrosis through downregulation of TGF-β1, MMP-9, TNF-α, and caspase-3 expression. In conclusion, eugenol nano-emulsion demonstrates promising anti-aging potential against cardiac complications by regulating mitochondrial dynamics, mitophagy, oxidative stress, inflammatory and apoptotic responses, and the SIRT1/TGF-β/MMP9 signaling pathway.

Molecular docking-guided discovery of Alhagi maurorum metabolites as dual-target biofungicides against Cercospora leaf spot in sugar beet - Reham I. Abdel Hamid; E. M. Naema Salama; Ibrahim S. H. El-Gamal; Samar A. M. Helmy; Mohamed Elshafiey; Ahmed G. Soliman; M. S. Abbas (Physiology and Molecular Biology of Plants, 2026)
Cercospora leaf spot (CLS), caused by Cercospora beticola , is a severe threat to sugar beet ( Beta vulgaris ) production in Egypt’s Nile Delta and poses resistance and ecological problems to synthetic fungicides. This study investigates Alhagi maurorum (camelthorn), an endemic medicinal shrub of arid regions, and evaluates it as a sustainable plant-sourced biofungicide for integrated CLS management. Following molecular confirmation of C. beticola (PCR amplified actin gene, 959 bp; ITS region sequenced and deposited in GenBank under accession PX884367), A. maurorum ethanolic extract (GC–MS) profiling of the ethyl iso-allocholate (1.39%), squalene (7.81%), and methyl oleate (27.33%) was determined as the antifungal constituents from GC–MS profiling. Molecular docking highlighted ethyl iso-allocholate’s dual inhibition of CYP51 (− 8.4 kcal/mol) and CHS (− 6.5 kcal/mol), critical for fungal ergosterol biosynthesis and cell wall integrity. In vitro assays demonstrated complete fungal suppression at 10% extract concentration, mirroring the synthetic fungicide Score®. The efficacy of the extract in controlling disease (66.4–71.5% disease control), along with increased root yield (34.23 tons/fed) and sucrose purity (91.81–92.38%) in two-season field trials, was validated in CLS endemic Kafr EL Sheikh. The biochemical analyses of treated plants showed elevated antioxidant defenses, reflected in phenolics (184.43–186.73 mg/g) and superoxide dismutase (SOD: 122.10–123.77 U/g), to protect the plants against oxidative stress. As an eco-friendly alternative to synthetic fungicides, the extract has biodegradability, pharmacokinetic suitability, and multi-target action. By bridging phytochemistry, computational biology, and field agronomy, this work advances integrated, climate-resilient strategies for CLS management and underscores the potential of arid-adapted plants in sustainable agriculture.

Ursolic acid, a pentacyclic triterpene from Ochrosia elliptica Labill leaves and its role in the management of polycystic ovary syndrome (PCOS) - Shimaa R. Emam; Marwa A. Ibrahim; Fady Sayed Youssef; Marwa S. Khattab; Riham A. El-Shiekh; Rehab A. Ghandour; Heba F. Hozyen; Marwa Zakaria; Essam A. Abdel-Sattar; Samar M. Mouneir (Inflammopharmacology, 2026)
Ursolic Acid (UA), a naturally occurring pentacyclic triterpene, was isolated from Ochrosia elliptica . Polycystic Ovary Syndrome (PCOS) a prevalent endocrine disorder characterized by hyperandrogenism, insulin resistance, and chronic inflammation. In this study, we investigate the role of UA in alleviating the symptoms of PCOS, focusing on its biochemical, hormonal, and histopathological effects in a rat model. Using adult female Wistar Albino rats, PCOS was induced through letrozole administration. The rats were then treated with UA at two different doses (25 and 50 mg/kg), alongside a control group and a standard ovulation-inducing medication, clomiphene citrate (1 mg/kg). Biochemical analyses showed that PCOS induction significantly increased serum malondialdehyde (MDA) levels by approximately 1.21-fold, while markedly reducing superoxide dismutase (SOD) and catalase (CAT) activities ( p ≤ 0.05) by approximately 0.48-fold, relative to negative control. Treatment with UA (50 mg/kg) dose-dependently restored oxidative balance, reducing MDA (~ 0.82-fold) and elevating SOD (~ 2.39-fold) and CAT (~ 2.11-fold) activities toward PCOS values ( p ≤ 0.05). Hormonally, PCOS rats exhibited elevated luteinizing hormone (LH) and testosterone levels by approximately 1.70-fold, compared to the negative control ( p ≤ 0.05). Both doses of UA significantly lowered LH and testosterone, with the 50 mg/kg dose achieving reductions comparable to clomiphene citrate ( p ≤ 0.05). Histopathological examination showed improved ovarian morphology with reduced cystic follicles and increased corpus lutea in UA-treated groups. Furthermore, UA downregulated key genes involved in steroidogenesis and oxidative stress response, suggesting a multifaceted mechanism of action. The findings highlight UA’s potential as a novel therapeutic option for managing PCOS symptoms, emphasizing the need for further research into its efficacy and safety in clinical applications.

Integrated computational and field approaches unveil nutrient foliar sprays as sustainable solutions for sugar beet powdery mildew management - M. S. Abbas; Ibrahim S. H. El-Gamal; Samar A. M. Helmy; Reham I. AbdelHamid (European Journal of Plant Pathology, 2026)
Sugar beet ( Beta vulgaris var. saccharum, L.), a primary contributor to the worldwide sugar market, suffers severely from powdery mildew caused by Erysiphe betae , which reduces the photosynthetic efficiency and therewith yields. This study presents molecular docking analysis and randomized complete block design (RCBD) field trials with nutrient foliar sprays to identify disease management strategies. The interaction study in silico analysis using AutoDock Vina indicated tight-binding interactions of metal sulfates with the chitinase enzyme that degrades the fungal cell wall, where the metal sulfates MgSO 4 (-4.03 kcal/mol) and ZnSO 4 (-3.88 kcal/mol) exhibited significant inhibitory effects. Under natural infection conditions for field validation, a significant reduction in disease severity was observed using copper sulfate (81.56% reduction), comparable to a commercial fungicide. Foliar applications of nutrients improved agronomic traits. Root yield increased by 38% and total sugar yield by 90% compared to un-treated controls. Biochemical analysis revealed significantly enhanced defense responses, including elevated levels of total phenols (76% increase with Copper Sulphate), increased enzymatic activities (peroxidase up to 0.482 U/min/g and catalase up to 0.725 U/min/g), higher protein content (up to 11.29 mg/g), and enhanced proline accumulation (up to 3.54 mg/g) compared to controls. This study highlights the promise of nutrient foliar applications as an environmentally sustainable approach that could replace conventional fungicides to control powdery mildew in sugar beet production.

Essential oils: antimicrobial, antioxidant properties, and their applications in food preservation—a comprehensive review - Dina Mostafa Mohammed; Maha B. Salem; Mohamed Elzallat; Samar Sami Alkafaas; Heba M. Salem; Fawze Alnadari; Essam H. Ibrahim; Amr Elkelish; Shaimaa H. Negm; Ahmed M. Saad; Synan F. AbuQamar; Khaled A. El-Tarabily; et al. (Phytochemistry Reviews, 2026)

Urban balcony gardens: exploring a resident-led nature-based solution - Salma N. Talhouk; Carine Ghassibe; Samar Morkos; Dany Abou Jaoude; Ibrahim Issa (Urban Ecosystems, 2026)

The Impact of Chronic Toxoplasmosis on the Gonadotropic Gonadal Axis in Male Rats - Samar Nagah El-Beshbishi; Soha Ibrahim Awad; Elham Farag Almeniar; Mona Younis Youssef; Nora Labeeb El-Tantawy; Amira Ibrahim Taman (Acta Parasitologica, 2026)

Unveiling the pharmacological potential of Agapanthus africanus: Antiviral, wound healing, anti-inflammatory activities, and lipid profile analysis - Alyaa Hatem Ibrahim Selim; Alshymaa Abdel-Rahman Gomaa; Naglaa Ahmed Mohamed Younis; Samar Yehia Desoukey (South African Journal of Botany, 2026)

Evaluation and selection of ground motion prediction equations for seismic hazard analysis in Northern Egypt - Samar Ghareeb; Rami Ibrahim; Toshiaki Yokoi; Mahmoud El-Hadidy; Mohsen M. Attia; Amr El-Sharkawy; Abdelbaset M. Abudeif (Journal of African Earth Sciences, 2026)

Mechanistic insights into the hepatoprotective role of rabeprazole against cyclophosphamide-induced hepatotoxicity via AMPK/SIRT1 activation and suppression of TLR4/NF-κB and MAPK pathways - Asmaa Saleh; Nahed A. Raslan; Heba Mohammed Refat M. Selim; Samar Ibrahim; Ahmed Mohamed Farghly; Abdel-Gawad S. Shalkami; Lamiaa A. Salama; Shaza M. Elhusseiny; Shaimaa M. Hafez; Nihal A. Mahmoud; Asmaa I. Alwakeel; Shimaa O. Ali; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Protective Role of Nano-encapsulated Bifidobacterium breve, Bacilllus coagulans, and Lactobacillus plantarum in Colitis Model: Insights Toward Propagation of Short-Chain Fatty Acids and Reduction of Exaggerated Inflammatory and Oxidative Response - Doaa Ibrahim; Safaa I. Khater; Hoda S. Sherkawy; Aya Elgamal; Asmaa A. Hasan; Asmaa A. Muhammed; Mohamed F. M. Farag; Samar A. Eissa; Tamer Ahmed Ismail; Hemmat M. Eissa; Areej A. Eskandrani; Wafa S. Alansari; et al. (Probiotics and Antimicrobial Proteins, 2025)

Targeting inflammation-driven tumor progression with Zafirlukast via modulation of Jagged-1/Notch-1/Hes-1, Wnt-4/β-catenin, and VEGF signaling pathways in mice - Asmaa Saleh; Dina F. Mansour; Nahed A. Raslan; Omneya Galal; Samar Ibrahim; Mohamed M. Hafez; Lubna Jamil; Shaza M. Elhusseiny; Heba Mohammed Refat M. Selim; Ahmed Mohamed Farghly; Hammad Yahia Abdoh; Lamiaa A. Salama; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Association of cell-free DNA, micro-RNA 21, and micro-RNA 146a levels with rheumatoid arthritis activity - Hend Moness; Reham Ali Ibrahim; Samar A. Soliman; Al-Shaimaa M. Abdel-Naiem; Shaimaa Moustafa Hafez; Noha M. Abdullah (Molecular Biology Reports, 2025)

Unveiling the pharmacological mechanisms of Spirulina platensis in rheumatoid arthritis rats through the integration of serum metabolomics, pathways analysis, and experimental validation - Dina S. Ghallab; Eman Shawky; Asmaa A. Khalifa; Samar S. Elblehi; Mohamed M. Mohyeldin; Reham S. Ibrahim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Rheumatoid arthritis (RA) is an autoimmune disease primarily manifested by insistent proliferative synovitis, joint degradation, and bone erosions with no targeted therapy yet. Spirulina platensis serves as a treasure house of bioactive compounds with potential significance against different inflammatory ailments. Inspired by the potentiating biological attributes of S. platensis , the current investigation is concerned with dissecting the mechanistic basis of S. platensis against rheumatoid arthritis (RA) through a series of biochemical and histopathological assessments integrated with a serum metabolomics strategy to explore more efficacious and safe alternative therapies to rectify RA. Firstly, a rat model of RA was established using complete Freund’s adjuvant (CFA), and RA-related biochemical and histopathological scores were determined as monitoring indexes for control efficiency of S. platensis against RA. Serum metabolomics was adopted to profile the potential biomarkers and their corresponding metabolic pathways modulated by Spirulina through UPLC-MS/MS analysis integrated with chemometrics and MetaboAnalyst 5.0 pathway analysis. The results demonstrated that Spirulina exerted significantly modulatory effects in the CFA model by reducing systemic manifestations of oxidative stress, inflammation, and impaired liver and kidney functions typically exemplified by catalase (CAT), superoxide dismutase (SOD), reduced glutathione (GSH), rheumatoid factor (RF), monocyte chemotactic protein 1 (MCP-1), tumor necrosis factor alpha (TNF-α), and interleukin-6 (IL-6), as well as alanine aminotransferase (ALT), aspartate aminotransferase (AST), creatinine, and urea. Histopathological investigations have revealed that Spirulina intervention causes moderately lower inflammatory cells infiltrations, synovial hyperplasia, and cartilage destruction. Regarding serum metabolomics, Spirulina could remarkably reverse disordered RA-associated metabolites, namely glutamic acid, arachidonic acid, 5-hydroxyeicosatetraenoic acid, (20:4/18:0) phosphatidylcholine, and citric acid, to a normal-like state through modulating arachidonic acid metabolism, alanine, aspartate and glutamate metabolism, and citrate cycle pathways putatively implicated in inflammation and joint damage. Our findings provide compelling evidence that S. platensis possesses a broad spectrum of mechanisms to restore the disrupted homeostasis in RA by multi-targeted, synergistic actions. Graphical abstract

Fluvastatin mitigates the testicular toxicity of Azathioprine via regulating mTOR pathway and restoring autophagy/apoptosis balance - Samar Sakr; Nahla M. Ibrahim; Basma A. Ibrahim; Ansam M. Z. El Desoky; Bassant T. Abd Elbaki; Mamdouh Eldesoqui; Zeinab A. Mohammed (Reproductive Toxicology, 2025)

The anti-inflammatory drugs diclofenac and ketorolac inhibit urease activity and biofilm formation by uropathogenic Proteus mirabilis - Afaf Eladl; Hisham A. Abbas; Samar S. Elbaramawi; Marwa Ibrahim Abd El-Hamid; Shaimaa I. Nazeih (Folia Microbiologica, 2025)
Proteus mirabilis is a major bacterium responsible for catheter-associated urinary tract infections (CAUTIs). Urease enzyme has a great role in the pathogenesis of Proteus mirabilis. Using urease, Proteus mirabilis can decompose urea to produce ammonia that increases urine pH and enhances crystal precipitation and crystalline biofilm formation. This leads to catheter blockage and pyelonephritis, respectively. Urease inhibitors are of great value in controlling this problem. Diclofenac sodium and ketorolac tromethamine, with their metal chelating activities, can inactivate urease by chelation of nickel ion in the active site of urease. This study investigated the ability of diclofenac sodium and ketorolac tromethamine to inhibit urease activity in Proteus mirabilis and crystalline biofilm formation. Diclofenac sodium and ketorolac tromethamine showed comparable activities against urease in cell lysates and whole cultures, with subsequent inhibition of pH increase and crystal formation in artificial urine. Diclofenac sodium showed higher biofilm inhibition and downregulation of urease genes ureR and ureC in RT-qPCR . The docking study showed the ability of both drugs to bind to urease enzyme and to chelate nickel ions in the active site of urease, suggesting that nickel chelation is the mode of inhibition of urease enzyme. In conclusion, diclofenac sodium and ketorolac tromethamine are two urease inhibitors that may be useful in treating Proteus mirabilis CAUTI .

Melatonin augments anti-tumor activity and alleviates nephrotoxicity of gemcitabine in a pancreatic cancer xenograft model targeting P62/Keap1 pathway - Samar Ibrahim; Eman H. Yousef; Ahmed M. El-Dessouki; Nahed A Raslan; Amany A. Alzokaky (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Although gemcitabine is a primary chemotherapy for pancreatic cancer, its effectiveness is limited by chemoresistance and nephrotoxicity, posing significant clinical challenges. Therefore, the development of novel therapeutic approaches to prevent pancreatic malignancy remains crucial. This study aimed to investigate the potential of melatonin in enhancing gemcitabine’s anticancer efficacy while mitigating its nephrotoxic effects through modulation of the Keap1/p62 pathway. A pancreatic cancer xenograft model was established in rats, which received either gemcitabine (50 mg/kg, I.P.), melatonin (50 mg/kg, I.P.), or their combination three times per week for 2 weeks. Our findings demonstrate that melatonin potentiates gemcitabine’s cancer-suppressing effects via modulation of the Kelch-like-ECH associated protein-1 (Keap1)/p62 pathway, resulting in reduced fibrosis, oxidative stress, and inflammatory markers. Additionally, melatonin significantly mitigated gemcitabine-induced nephrotoxicity. These results suggest that melatonin may serve as an adjuvant therapy in pancreatic cancer treatment, enhancing chemotherapy efficacy while reducing its adverse effects.

Mycological and molecular identification of mycoses involved in mastitis from Holstein dairy cattle with special reference to Candida albicans - Hayat Fayed; Asmaa A. Elgendy; Salma A. Shoulah; Samar M. Moustafa; Ahmed Maher; Ahmed F. Hikal; Ahmed Abdeen; Ekramy Elmorsy; Mohamed E. Mohamed; Helal F. Hetta; Heba Allah Elbaghdady; Afrina Mustari; et al. (Veterinary Research Communications, 2025)

Febuxostat protects from Doxorubicin induced hepatotoxicity in rats via regulation of NF-κB p65/NLRP3 inflammasome and SIRT-1/AMPK pathways - Ahmed M. El-Dessouki; Eman H. Yousef; Nahed A. Raslan; Asmaa I. Alwakeel; Samar Ibrahim; Amany A. Alzokaky (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Doxorubicin (DOX) is a highly potent broad-spectrum anticancer drug, but it has severe side effects, including hepatotoxicity. Therefore, we evaluated the efficacy of febuxostat (FBX), a specific inhibitor of xanthine oxidase and antioxidant, in blocking hepatotoxicity associated with DOX in rats. Rats were treated with FBX (10 or 15 mg/kg/day orally for 2 weeks) and given DOX (15 mg/kg as single dose at the 7th day, intraperitoneal) to induce hepatotoxicity. The results indicated that FBX could reduce the pathological alterations of liver tissues induced by DOX and ameliorate the inappropriate changes in liver function biomarkers (AST, ALT, and ALP) in serum, oxidative stress parameters (catalase, superoxide dismutase, NOX1, NQO-1, HO-1, Keap-1, and Nrf2) and inflammatory markers in the liver (NF-κB p65, TNF-α, NLRP3). Additionally, FBX attenuated the p53, BAX, cytochrome C, caspase-9, and caspase-3 levels to restrain cell apoptosis. In addition, FBX therapy was found to increase protein levels of SIRT-1 and AMPK in the liver. These findings demonstrate that FBX can reduce the hepatotoxicity caused by DOX in rats through mechanisms that counteract oxidative stress, inflammation, and apoptosis.

Effects of short-term supplementation with Amphora coffeaeformis post Aeromonas sobria infection on immune response, health, and survival of Nile tilapia (Oreochromis niloticus) - Hosny A Ibrahim; Rasha M. Reda; Azza AA Galal; Shahira H. Mahmoud; Mohamed M. M. Metwally; Samar H. Abdallah (Journal of Applied Phycology, 2025)
Previous studies have focused on long-term dietary supplementation of fish with the diatom Amphora coffeaeformis to prevent infections. This study introduces a novel approach by assessing short-term post-infection administration of A. coffeaeformis to mitigate Aeromonas sobria infection in Nile tilapia ( Oreochromis niloticus ). This approach addresses the need for sustainable strategies to manage infections after onset, reducing reliance on antibiotics. The effects of A. coffeaeformis on hepatic-renal function, antioxidant-immune response, and histopathological alterations were evaluated. Two hundred and ten O. niloticus were distributed into seven groups. The first group (CONT) was injected intraperitoneally with sterile tryptic soy broth (0.2 mL) and fed a basic diet. The remaining six groups were injected with A. sobria (1.5 x 10⁷ CFU, 0.2 mL) and fed a control-based diet until clinical signs appeared. Subsequently, the second group (I) fed a basic diet. The third (I+AMP50) and fourth (I+AMP70) received diets containing A. coffeaeformis powder at 50 or 70 g kg -1 , respectively. The fifth (I+AME50) and sixth (I+AME70) groups received diets containing 50 or 70 g kg -1 of A. coffeaeformis extract, while the seventh group (I+OXY) received 500 mg kg -1 of oxytetracycline. The infected fish treated with A. coffeaeformis extract, particularly at 70 g kg -1 (AME70), exhibited significantly improved hematological and histopathological profiles, as well as improved liver and kidney function, antioxidant responses, and immune responses. This study highlights the potential of short-term post-infection supplementation with A. coffeaeformis , particularly AME at 70 g kg -1 , as a sustainable alternative to antibiotics for managing A. sobria infections in aquaculture.

Dabigatran attenuates methotrexate-induced hepatotoxicity by regulating coagulation, endothelial dysfunction, and the NF-kB/IL-1β/MCP-1 and TLR4/NLRP3 signaling pathways - Ahmed M. El-Dessouki; Amany A. Alzokaky; Nahed A. Raslan; Samar Ibrahim; Heba Mohammed Refat M. Selim; Ahmed A. Al-Karmalawy (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Efficacy of Amphora coffeaeformis supplemented diets in improving growth performance, health status, and resistance to Aeromonas sobria in Oreochromis niloticus exposed to suboptimal temperature conditions - Hosny A. Ibrahim; Rasha M. Reda; Azza A. A. Galal; Shahira H. Mahmoud; Samar H. Abdallah (Journal of Applied Phycology, 2025)
Climate change affects aquaculture to a significant extent, while one of the primary threats to Nile tilapia ( Oreochromis niloticus ) growth and health is suboptimal temperatures. The objective of this study was to assess the effects of Amphora coffeaeformis powder and extract on the growth performance and health status of tilapia grown in suboptimal temperature (21 °C). A total of 180 fish (31.39 ± 0.5 g) were randomly allocated into six groups, each with three replicates. The control group was fed a basal diet. The second and third groups were supplemented with 50 g kg −1 (AMP50) and 70 g kg −1 (AMP70) of A. coffeaeformis powder, respectively. The fourth and fifth groups received 50 g kg −1 (AME50) and 70 g kg −1 (AME70) of A. coffeaeformis extract, respectively. The sixth group (OXY) was fed a diet with 500 mg kg⁻ 1 of oxytetracycline. After a 60-day feeding trial, all fish were challenged with Aeromonas sobria . The findings indicated that the extract of A. coffeaeformis , particularly at a concentration of 70 g kg −1 diet, significantly enhanced growth performance, hematological and biochemical parameters, antioxidant and immunological markers. Additionally, it notably increased resistance against A. sobria . These results suggest that A. coffeaeformis supplementation, particularly AME at 70 g kg −1 , effectively mitigates suboptimal temperature effects on Nile tilapia productivity by enhancing growth, health, and disease resistance.

The ability of dietary essential oils to mitigate nickel-induced growth retardation, immune-antioxidant suppression, and endoplasmic reticulum stress activation in Nile tilapia - Shaimaa A. A. Ahmed; Ghada I. Abd El-Rahman; Haiam A. Mohammed; Samar A. Abdo; Mohamed Y. M. Aly; Hala Elshahat Ghannam; Fatma Mahsoub; Tarek Khamis; Rowida E. Ibrahim (Fish Physiology and Biochemistry, 2025)
Fish immunity is significantly impacted by waterborne metal intoxication. Nickel is a ubiquitous metal in aquatic bodies which badly impacts fish immune responses and survival. In the current research, we looked into the possible protective effects of essential oils of tea tree (TTO) and basil (BEO) against nickel exposure in Nile tilapia, or Oreochromis niloticus . To achieve this, 240 Nile tilapia (27.92 ± 0.22 g) were categorized into six groups for 45 days; three groups were fed on basal control, TTO, and BEO diets without Ni exposure. The other three groups were subjected to Ni at a level of 3.6 mg/L and fed on basal, TTO, and BEO diets. The outcomes showed a substantial decrease in the growth measures and survival % in the Ni-exposed fish. Oxidative stress (higher splenic malondialdehyde and lower splenic catalase, reduced glutathione, and superoxide dismutase), immune suppression (lower serum lysozyme, myeloperoxidase, and nitric oxide), and elevated serum cortisol levels were observed in the Ni-intoxicated group. The Ni-intoxicated group exhibited various pathological alterations detected in the intestinal tissue mainly inflammatory and necrotic changes, moreover, moderate depletion of lymphoid elements represented by necrotic lymphocytes in the splenic tissue. Ni-exposure induced endoplasmic reticulum stress through up-regulation of the splenic expression of protein kinase R-like endoplasmic reticulum kinase, activating transcription factor 6, CCAAT/enhancer-binding protein homologous protein, X-box binding protein 1, α-subunit of eukaryotic initiation factor 2, inositol-requiring kinase 1a, mitogen-activated protein kinase, c-JunN-terminal kinase, and binding protein for immunoglobulins. Feeding on the TTO and BEO diets improved the growth measures, survival, and antioxidant capacity. Immunomodulation, enhancement of the intestinal and splenic architecture, and relief of the endoplasmic reticulum stress condition were noticed when the Ni-intoxicant groups were fed on TTO and BEO diets. Overall, the effect of the TTO diet was more pronounced than the BEO diet in mitigating the negative consequences of Ni-intoxication in Nile tilapia. Dietary fortification of 0.1% TTO and/or 0.1% BEO is recommended during Ni exposure in aquaculture practices.

Evolutionary and dispersal dynamics in invasive races of Puccinia striiformis f. sp. tritici attributed to virulence and SCAR markers - Samar M. Esmail; Ibrahim S. Draz; Mohamed D. Sehsah; Heba I. Saad-El-Din; Wassief A. Youssef; Doaa A. Komeil (Physiological and Molecular Plant Pathology, 2025)

Antagonistic Effect of Zinc Oxide Nanoparticles Dietary Supplementation Against Chronic Copper Waterborne Exposure on Growth, Behavioral, Biochemical, and Gene Expression Alterations of African Catfish, Clarias gariepinus (Burchell, 1822) - Shaimaa A. A. Ahmed; Rowida E. Ibrahim; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Khaled Yehia Faroh; Samar A. El Gamal; Shereen Badr; Tarek Khamis; Abdallah Tageldein Mansour; Simon J. Davies; Mohamed ElHady (Biological Trace Element Research, 2024)

Evaluating the persistence and insecticidal effects of emulsifiable concentrate containing Cananga odorata essential oil on survival and enzymatic activity of Spodoptera littoralis - Samar Sayed Ibrahim; Elham Ahmed Sammour (Phytoparasitica, 2024)
The essential oil of Cananga odorata was prepared as an emulsifiable concentrate formulation and examined for its insecticidal activity against Spodoptera littoralis larvae. The effectiveness of C. odorata oil in both pure and EC formulations was investigated in terms of enzymatic activity and survival. In addition, their persistence effect was studied in semi-field conditions. Benzyl benzoate (18.86%), benzyl acetate (9.18%), β-Maaliene (15.53%), alloaromadendrene (6.41%), cis-Thujopsene (6.16%), cedrene (5.35%), and benzyl alcohol (5.98%) were the most abundant compounds found in C. odorata oil by gas chromatography-mass spectrometry analysis. The EC formulation exhibited the highest toxicity and produced LC values of 0.47, 1.02, and 3.78% for LC 40 , LC 50 , and LC 90 , respectively, compared to 1.05, 1.70, and 4.96%, respectively, resulted from pure oil after 72 h of exposure. Following EC application, the mean survival time was only 3.60 ± 0.57 days, compared to pure oil treatment (7.70 ± 1.11 days) and control (14.0 ± 0.0 days). The LC 40 of EC formulation induced a more potent inhibitory effect for the detoxification enzyme carboxylesterases (CarE; α- and β-esterase) and the oxidative stress enzyme superoxide dismutase (SOD). Under semi-field conditions, the cumulative mortality of S. littoralis larvae increased by increasing the exposure time to LC 90 of both formulations. The EC formulation had the highest mortality rates for the total exposure period (7 days). According to these results, C. odorata EC formulation demonstrated enhanced toxicity and persistence effects, and it can be utilized as a green bio-insecticide for the management of S. littoralis larvae.

Molecular mechanisms underlying cyclophosphamide-induced cognitive impairment and strategies for neuroprotection in preclinical models - Kamilia M. Ibrahim; Samar F. Darwish; Eman M. Mantawy; Ebtehal El-demerdash (Molecular and Cellular Biochemistry, 2024)
Cyclophosphamide has drastically enhanced the expectancy and quality of life of cancer patients. However, it is accompanied by diverse neurological complications which are considered a dose-limiting adverse effect. Neurotoxicity caused by cyclophosphamide can manifest in numerous manners including anxiety, depression, motor dysfunction and cognitive deficits. This review article offers an overview on cyclophosphamide-induced neurotoxicity, providing a unified point of view on the possible underlying molecular mechanisms including oxidative brain damage, neuroinflammation, apoptotic neuronal cell death as well as disruption of the balance of brain neurotransmitters and neurotrophic factors. Besides, this review sheds light on the promising protective agents that have been investigated using preclinical animal models as well as their biological targets and protection mechanisms. Despite promising results in experimental models, none of these agents has been studied in clinical trials. Thus, there is lack of evidence to advocate the use of any neuroprotective agent in the clinical setting. Furthermore, none of the protective agents has been evaluated for its effect on the anticancer activity of cyclophosphamide in tumor-bearing animals. Therefore, there is a great necessity for adequate well-designed clinical studies for evaluation of the therapeutic values of these candidates. Conclusively, this review summarizes the molecular mechanisms accounting for cyclophosphamide-induced neurotoxicity together with the potential protective strategies seeking for downgrading this neurological complication, thus enhancing the quality of life and well-being of cancer patients treated with cyclophosphamide. Graphical abstract

Phytochemical characterization and biological evaluation of Agapanthus africanus: A combined experimental and in silico study - Alshymaa Abdel-Rahman Gomaa; Naglaa Ahmed Mohamed Younis; Heba A. Hofny; Samar Yehia Desoukey; Alyaa Hatem Ibrahim Selim (South African Journal of Botany, 2024)

Phenotypic and molecular characterization of pleiotropic resistance to rusts and powdery mildew in spring wheat - Ibrahim S. Draz; Samar M. Esmail; Doaa A. Komeil (Euphytica, 2024)
An attempt was undertaken to comprehend how phenotypic markers, leaf tip necrosis (LTN), and pseudo black chaff (PBC), are associated with pleiotropic resistance genes in wheat ( Triticum spp.). Pleiotropic resistance to stripe rust ( Puccinia striiformis f. sp. tritici ), leaf rust ( P. triticina ), stem rust ( P. graminis f. sp. tritici ) and powdery mildew ( Blumeria graminis f. sp. tritici ) was evaluated in 57 Egyptian spring wheat cultivars at seedling stage in greenhouse and at adult plant stage in field during 2021/22 and 2022/23. At seedling stage, pleiotropic resistance rated moderately resistance (MR) was observed in five cultivars, Misr-3 (all three rusts), Misr-4 (stripe rust, leaf rust, powdery mildew), Giza-168 (leaf rust, stem rust, powdery mildew), Sakha-94 and Sids-13 (leaf rust, stem rust). At adult plant stage, Misr-4 outperformed all other evaluated cultivars, exhibiting a high level of pleiotropic adult plant resistance (PAPR) against all diseases investigated. High levels of PAPR were also noticed against the three rusts in nine cultivars, Misr-3, Sakha-93, Sakha-94, Sakha-95, Giza-156, Giza-168, Giza-171, Gemmeiza-10 and Sids-13, and moderate levels against powdery mildew in Misr-3, Sakha-95, Giza-156. Four PAPR genes were characterized in cultivars based on phenotypic and molecular markers. Phenotypic markers (LTN and PBC) were observed in 23 cultivars. Molecular marker csLV34 indicated the presence of Lr34/Yr18/Sr57/Pm38/Ltn1 in six cultivars, whilst marker Xwmc44 indicated that Lr46/Yr29/Sr58/Pm39/Ltn2 was present in five cultivars. Marker Xcfd71 indicated the presence of Lr67/Yr46/Sr55/Pm46/Ltn3 in 19 cultivars. Gene Sr2/Yr30/Lr27/Pbc was identified with marker csSr2 in three cultivars. A complete association between LTN and molecular markers was recorded, while a strong association ( r = 0.73) was recorded between PBC and molecular markers. Findings demonstrated the reliability of phenotypic markers in predicting pleiotropic resistance in wheat, which would facilitate marker-assisted selection in breeding programs.

Examining the effect of different photovoltaic modules on cucumber crops in a greenhouse agrivoltaic system: A case study - Nabeel Gnayem; Esther Magadley; Alaa Haj-Yahya; Samar Masalha; Ragheb Kabha; Alhan Abasi; Hani Barhom; Madhat Matar; Mohammed Attrash; Ibrahim Yehia (Biosystems Engineering, 2024)

Phylogenesis of virulent races of Puccinia graminis f. sp. tritici based on phenotyping and genotyping using newly developed SNP markers for genetic groups in clades - Samar M. Esmail; Ibrahim S. Draz; Doaa R. El-Naggar; Diaa Abd El-Moneim; Salha M. Alshamrani; Tahiyat Alothaim; Maryam M. Alomran; Les J. Szabo (Physiological and Molecular Plant Pathology, 2024)

A comparative novel green reversed-phase high-performance liquid chromatography method for simultaneous determination of ivabradine and carvedilol in tablets and human plasma using UV and fluorescence detectors - Ethar A. Rashad; Samar S. Elsayed; Jenny Jeehan M. Nasr; Fawzia A. Ibrahim (Sustainable Chemistry and Pharmacy, 2024)

Rhizospheric Addition of Hydrogel Polymer and Zeolite Plus Glutathione Mitigate the Hazard Effects of Water Deficiency On Common Bean Plants Through Enhancing the Defensive Antioxidants - Samar M. A. Doklega; Hani S. Saudy; M. A. El-Sherpiny; Ahmed Abou El-Yazied; Hany G. Abd El-Gawad; Mohamed F. M. Ibrahim; Mahmoud A. M. Abd El-Hady; Mohamed M. A. Omar; Amr A. Metwally (Journal of Crop Health, 2024)
Currently, the world is facing many troubles in crop production and the irrigation water deficit is the most harmful among them. Saving irrigation water is the main target for all countries of the world, especially in arid areas. Field trial was executed aiming to assess the influence of irrigation regimes (100, 80 and 60% of irrigation requirements, IR (IR 100 , IR 80 and IR 60 , respectively), water-absorbent substances (control, hydrogel polymer and zeolite as soil addition) and foliar application of glutathione (GSH) [with GSH or without] on the performance of common bean plants. Findings clarified that plant fresh weight obtained with the combination of IR 80 × zeolite × GSH had no significant differences with the superior combination of IR 100 × hydrogel polymer or zeolite × GSH. Hydrogel polymer plus GSH supply showed distinctive enhancements for N, P and K accumulation in common bean leaves. Application of zeolite plus GSH reduced the accumulation of POX and CAT by 21.8 and 15.5% under IR 80 and 16.1 and 7.6% under IR 60 , respectively. Spraying of GSH × hydrogel polymer under IR 100, IR 80 and IR 60 significantly increased the value of pods yield by 26.5%, 25.23% and 32.80, respectively, as compared to corresponding control treatment. the interaction of IR 100 and hydrogel polymer whether with or without GSH showed the highest significant values of N, P, protein, fiber, carbohydrates percentages and TDS. Briefly, it can be concluded that water holding amendments i.e., polymer and zeolite as well as low-molecular-weight antioxidants i.e., glutathione can mitigate the hazard impacts of elevated reactive oxygen species production under drought. Practically, common bean growers are advised to treat the soil with available soil amendment (hydrogel polymer, 0.24 t ha −1 or zeolite, 1.20 t ha −1 ) and spraying common bean plants by glutathione, 1.0 mM to sustain the crop productivity and quality under shortage water conditions

Adrenergic receptors blockade alleviates dexamethasone-induced neurotoxicity in adult male Wistar rats: Distinct effects on β-arrestin2 expression and molecular markers of neural injury - Rasha M. S. M. Mohamed; Enssaf Ahmad Ahmad; Dalia M. Amin; Samar Ahmed Abdo; Islam A. A. E.-H. Ibrahim; Mona F. Mahmoud; Shimaa Abdelaal (DARU Journal of Pharmaceutical Sciences, 2023)
Background Dexamethasone-induced neurotoxicity has been previously reported. However, the molecular mechanisms are still not completely understood. Objectives The current work aimed to investigate the modulatory effects of α- and β-adrenergic receptors on dexamethasone-induced neurotoxicity in rats focused on changes in β-arrestin2 and molecular markers of neural injury in cerebral cortex. Methods Male Wistar rats were subcutaneously injected with dexamethasone (10 mg/kg/day) for 7 days to induce neural injury in the cerebral cortex. The experiment involved 5 groups: control, dexamethasone, carvedilol, propranolol, and doxazosin. In the last 3 groups, drugs were given 2 hours before dexamethasone injection. At the end of experiment, brain samples were collected for measurement of brain derived neurotrophic factor (BDNF), glial fibrillary acidic protein (GFAP), kinase activity of protein kinase B (Akt), diacylglycerol (DAG), α-smooth muscle actin (α-SMA), Smad3, β-amyloid and phospho-tau protein levels in addition to histopathological examination of brain tissue using hematoxylin-eosin, Nissl, and Sirius red stains. Moreover, β-arrestin2 levels in the cerebral cortex were measured using immunohistochemical examination. Results Dexamethasone slightly reduced brain weight and significantly decreased BDNF, Akt kinase activity and β-arrestin2 but markedly induced degeneration of cortical neurons and significantly increased GFAP, DAG, α-SMA, Smad3, β-amyloid and phospho-tau protein levels compared to controls. Carvedilol, propranolol, and doxazosin reversed all dexamethasone-induced molecular changes and slightly ameliorated the histopathological changes. Carvedilol significantly increased brain weight and β-arrestin2 levels compared to dexamethasone, propranolol, and doxazosin groups. Conclusion blocking α- and/or β-adrenergic receptors alleviate dexamethasone-induced neurotoxicity despite their distinct effects on β-arrestin2 levels in the cerebral cortex. Graphical abstract

Metabolic profiling and biological potential of the marine sponge associated Nocardiopsis sp. UR67 along with docking studies - Alyaa Hatem Ibrahim; Eman Zekry Attia; Heba A. Hofny; Faisal Alsenani; Ahmed Zayed; Mostafa E. Rateb; Usama Ramadan Abdelmohsen; Samar Yehia Desoukey; Mostafa Ahmed Fouad; Mohamed Salah Kamel (Natural Product Research, 2023)

Kidney bean protein hydrolysate as a fish meal replacer: Effects on growth, digestive enzymes, metabolic functions, immune-antioxidant parameters and their related gene expression, intestinal and muscular gene expression - Rowida E. Ibrahim; Samar A. Tolba; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Shimaa I. Shalaby; Ali Osman; Tarek Khamis; Mohamed A. Eissa; Simon J. Davies; Shimaa A. Amer (Aquaculture, 2023)

Sponge-like zinc oxide nanoparticles loaded xanthan gum/cationic chitosan cryogel: Synthesis, characterization, microbicidal and adsorption of synthetic dye and heavy metal - Samar A. El-Kholy; Emad K. Radwan; Mehrez E. El-Naggar; Shaimaa T. El-Wakeel; Ibrahim El-Tantawy El Sayed (Journal of Environmental Chemical Engineering, 2023)

Correction to: Potential suppression of broad-spectrum virulence of Blumeria graminis f. sp. tritici population to race-specific resistance genes in hexaploid wheat - Ibrahim S. Draz; Abdelrazek S. Abdelrhim; Ola I. Mabrouk; Samar M. Esmail (Journal of Plant Pathology, 2023)

Potential suppression of broad-spectrum virulence of Blumeria graminis f. sp. tritici population to race-specific resistance genes in hexaploid wheat - Ibrahim S. Draz; Abdelrazek S. Abdelrhim; Ola I. Mabrouk; Samar M. Esmail (Journal of Plant Pathology, 2023)
Powdery mildew caused by Blumeria graminis f. sp. tritici ( Bgt ), is one of the serious diseases that attack wheat plants during the growing season. The Bgt virulence was screened against 16 Egyptian wheat cultivars and 21 powdery mildew differential lines carrying different ( Pm ) resistance genes in two regions (Kafr-Elsheikh and El-Minya) in Egypt 2021–2022. Broad-spectrum virulence and high diversity were observed at both regions. Regional populations of Bgt in Egypt are independent of each other. Genes, Pm2a, Pm3a, Pm1b, Pm3b, Pm21, Pm34, Pm36, Pm37, Pm53, PmNCA6, PmMIAG12, and PmNCAG13 were nationally effective, while Pm4a, Pm4b , Pm6 , and Pm8 appeared to be defeated throughout the country affected by broad-spectrum virulence. Field responses showed that only four cultivars, Misr-1, Misr-2, Sakha-95 and Shandweel-1 were resistant in both regions. A strong correlation was recorded between FDS and AUDPC which implies that wheat pathologists and breeders may be able to assess their lines by a single scoring at an appropriate time. Phenotypic and genotypic data proved that ineffective Pm8 was present in four susceptible cultivars, Sakha-93, Sakha-94, Gemmeiza-10, and Gemmeiza-11, while it was present in combination with effective Pm3a in two resistant cultivars, Sakha-95 and Shandweel-1. This suggests that cultivar susceptibility may be attributed to the existence of ineffective gene Pm8 potentially suppressed by effective Pm3a in hexaploid-resistant wheat. Pyramiding effective resistance genes particularly those that have a suppression effect like Pm3a may be a viable option to avoid the risk of broad-spectrum Bgt virulence at a regional scale.

Effect of Spirulina platensis on growth, hematological, biochemical, and immunological parameters of Nile tilapia (Oreochromis niloticus) - Ibrahim M. I. Youssef; Elham S. E. Saleh; Samar S. Tawfeek; Asmaa A. A. Abdel-Fadeel; Abdel-Razik H. Abdel-Razik; Asmaa S. A. Abdel-Daim (Tropical Animal Health and Production, 2023)
This study was conducted to evaluate the effects of Spirulina platensis in Nile tilapia diets on growth performance, blood hematological and biochemical parameters, immunological status, and intestinal histomorphometry. A total of 228 fish were randomly allocated into four groups with triplicates (19 fish per replicate). The first group was fed the control diet, which contained no Spirulina supplementation. The other three groups were fed diets containing graded levels of powdered Spirulina: 2.5%, 5.0%, and 10.0% in the second, third, and fourth group, respectively. S. platensis was added to the diets partially substituting the fish meal content. The experiment lasted for 8 weeks. The results showed that dietary Spirulina supplementation improved ( P < 0.05) the body weight and length, weight gain, specific growth rate, condition factor, and feed conversion efficiency. Moreover, Spirulina increased significantly ( P < 0.05) the hemoglobin, PCV, RBCs, and WBCs count. Also, it increased the lymphocytes, eosinophils, IgM level, lysozyme activity, and phagocytic activity in the blood. Additionally, the Spirulina raised ( P < 0.05) the serum albumin level but reduced ( P < 0.05) the creatinine and urea levels. The addition of Spirulina increased ( P < 0.05) the height and width of intestinal villi and the lymphocytes and goblet cells count in the intestine. The obtained results were increased by increasing the inclusion level of Spirulina, especially for body weight and length, weight gain, FCR, phagocytic activity, and intestinal parameters. In conclusion, supplementing S. platensis can improve the growth performance of fish. Moreover, it can stimulate the immunity of fish through increasing the level of immunological blood indicators (IgM, lysozyme, phagocytic activity, lymphocytes, and eosinophils) as well as the local intestinal immunity (lymphocytes and goblet cells). So, it can be recommended to use S. platensis in fish diets not only to improve the growth performance but also to enhance the immune status.

Metabolic and genotypic mechanisms involved in early defensive response of powdery mildew-infected wheat - Khairiah M. Alwutayd; Samar M. Esmail; Heba I. Saad-El-Din; Diaa Abd El-moneim; Ibrahim S. Draz (Physiological and Molecular Plant Pathology, 2023)

Ceratonia siliqua pods (Carob) methanol extract alleviates doxorubicin-induced nephrotoxicity via antioxidant, anti-inflammatory and anti-apoptotic pathways in rats - Attia H. Atta; Shimaa A. Atta; Marwa S. Khattab; Tamer H. Abd El-Aziz; Samar M. Mouneir; Marwa A. Ibrahim; Soad M. Nasr; Shimaa R. Emam (Environmental Science and Pollution Research, 2023)
Doxorubicin (DOX) is an anti-neoplastic therapy, but its use is limited by its deleterious toxic effects including nephrotoxicity and cardiotoxicity. This work aimed at assessing the potential protective effect of Ceratonia siliqua methanol extract (CME) on DOX-induced nephrotoxicity in 5 groups of Wistar rats. Nephrotoxicity was induced experimentally by intraperitoneal (IP) injection of DOX (15 mg/kg). DOX increased serum creatinine, urea, sodium, and potassium levels. It elevated MDA levels in the renal tissue but decreased the concentration of GSH and the activity of GST, CAT, and SOD. Meanwhile, it decreased the level of immunomodulatory anti-inflammatory mediators: IL-10 and TGF-β, as well as the activity of MPO but increased the level of IL-6, TNF-α, and caspase-3 in the renal tissue. DOX has upregulated COX-2, caspase-9, and Bax gene expression and downregulated the Bcl-2 gene expression. Immunolabeling of renal tubular epithelium in DOX-intoxicated rats was moderate to strong against Bax, COX-2, and NF-kβ and weak against Bcl-2. Treatment with CME significantly restored the levels of kidney function parameters and the levels of oxidative stress markers. It stimulated the production of IL-10 and TGF-β and decreased the level of IL-6 and TNF-α. CME reverted the gene expression of COX-2, caspase-9, and Bax. Microscopically, CME alleviated the DOX-induced renal damage. Phytochemical analysis revealed the presence of 26 compounds in the CME. No signs of acute toxicity were recorded by CME up to 4000 mg/kg b. wt. orally into mice. Finally, CME could effectively alleviate the deleterious effects of DOX on the kidney. The safety of carob extract encourages its use in the preparation of valuable therapeutic agents.

The involvement of antioxidant, stress, and immune-related genes in the responsive mechanisms of common carp (Cyprinus carpio) to hypersalinity exposure - Hassan Ahmed; Karima A. Bakry; Ahmed Abdeen; Halla E. K. El bahgy; Mohamed Abdo; Florin Imbrea; Liana Fericean; Mona A. Elshemy; Samah F. Ibrahim; Mustafa Shukry; Samar H. Baloza; Walaa F. A. Emeish (Frontiers in Marine Science, 2023)
Salinity stress is one of the marked influencing factors on the ecophysiology of aquaculture and is considered an important reason for the retreat of the fish industry. The current study is an endeavor to elucidate the molecular mechanisms that underlie the response to salinity stress in common carp. Fish (Average weight 5 ± 2 g) were randomly distributed into two groups; the 1 st is a control was exposed to tap water (0.2 ppt salinity) and the 2 nd is a treated was exposed to hypersalinity (10 ppt salinity) for five days. Serum biochemical indicators including total protein, albumin, globulins, A/G ratio, blood glucose, cortisone, Na + , K + , and Cl - levels were evaluated. Besides, Tumor necrosis factor-α, interleukin-1β, corticotropin-releasing hormone, and catalase enzyme mRNA expression levels were assessed in lymphoid and immunocompetent organs (liver and spleen) and osmoregulatory organs (kidney and gills) by using Real-time qPCR. Hypersalinity adversely affected the biochemical markers; total protein, albumin, and globulins decreased significantly; however, blood glucose, serum cortisol, and sodium markedly increased in fish exposed to hypersalinity compared with the control. In addition, from the molecular point of view, all the evaluated genes were upregulated at a high expression rate in the liver compared with other studied organs after the salinity challenge. On the contrary, hypersalinity modulated the expression of immune-related genes (Tumor necrosis factor-α and interleukin-1β) in the kidney and spleen and upregulated corticotropin-releasing hormone mRNA in all studied organs except gills. In conclusion, the obtained data clarified the molecular and biochemical mechanisms of salinity stress on the liver, kidney, spleen, and gills. Furthermore, it strongly suggests the implication of neural, endocrine, and immune systems in the responsive mechanisms to the salinity stress in carp.

Application of Bentonite Clay, Date Pit, and Chitosan Nanoparticles as Promising Adsorbents to Sequester Toxic Lead and Cadmium from Milk - Amany Abdelnaby; Nabila M. Abdelaleem; Elham Elshewy; Ayman H. Mansour; Samar S. Ibrahim (Biological Trace Element Research, 2023)
Evaluating residual lead (Pb) and cadmium (Cd) levels in food products, especially milk, is critical for product safety and quality. In this purview, the current study aims to determine Pb and Cd concentrations in milk using atomic absorption spectrophotometry and compare their values with international standards. In addition, it aims to remove these metals from milk samples using low-cost, naturally occurring materials, such as bentonite, date pit, and chitosan nanoparticles. The ability of potential adsorbents was also investigated using Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray (EDX), and transmission electron microscope (TEM). Moreover, their impact on milk’s nutritional properties was considered. The results revealed that most milk samples contained Pb and Cd, with mean values of 0.237 ± 0.179 and 0.041 ± 0.036 mg/kg, respectively. Furthermore, the three possible adsorbents demonstrated high sequestering ability due to their existing functional groups; the adsorption capacity of bentonite to Pb and Cd was 84 and 88%, date pit was 97 and 93%, and chitosan nanoparticles were 82 and 98%, respectively, with no discernible change in milk nutritional contents. In conclusion, the bentonite, date pit, and chitosan nanoparticles were found to be significantly effective and safe in removing hazardous trace elements (Pb and Cd) from contaminated milk. Graphical abstract

Stem rust appraisal of local and global wheat germplasm with a new virulence threat to resistance genes - Mohamed A. Abou-Zeid; Ola I. Mabrouk; Ibrahim S. Draz; Heba I. Saad-El-Din; Fatmah A. Safhi; Salha M. ALshamrani; Samar M. Esmail (Australasian Plant Pathology, 2023)

Nanotechnology as a tool for abiotic stress mitigation in horticultural crops - Ibrahim M. Abdelsalam; Soumya Ghosh; Samar Sami AlKafaas; Heba Bedair; Alhadji Malloum; Sara Samy ElKafas; Khalil M. Saad-Allah (Biologia, 2022)

Potential implementation of trees to remediate contaminated soil in Egypt - Heba Bedair; Soumya Ghosh; Ibrahim M. Abdelsalam; Ayaz Ali Keerio; Samar Sami AlKafaas (Environmental Science and Pollution Research, 2022)

The efficacy of clay bentonite, date pit, and chitosan nanoparticles in the detoxification of aflatoxin M1 and ochratoxin A from milk - Amany Abdelnaby; Nabila M. Abdelaleem; Elham Elshewy; Ayman H. Mansour; Samar Ibrahim (Environmental Science and Pollution Research, 2022)

Bioremediation role of Spirulina platensis against deltamethrin-mediated toxicity and its chemical residues in chicken meat - Samar Saber Ibrahim; Rasha Elsabagh; Ali Allam; Gehan Youssef; Sabreen Ezzat Fadl; Ehab Yahya Abdelhiee; Mohamed Alkafafy; Ahmed Soliman; Mohamed Aboubakr (Environmental Science and Pollution Research, 2021)

Effect of Garlic and Lemongrass Essential Oils on Some Biological and Biochemical Aspects of Corn Stem Borer Sesamia cretica Larvae (Lepidoptera: Noctuidae) During Diapausing Phase - Elham Ahmed Abdel-Hakim; Samar Sayed Ibrahim; Nagwa Yousef Salem (Proceedings of the Zoological Society, 2021)

Correction to: The effect of exosomes derived from mesenchymal stem cells in the treatment of induced type 1 diabetes mellitus in rats - Dina Sabry; Samar Marzouk; Reem Zakaria; Heba A. Ibrahim; Mai Samir (Biotechnology Letters, 2020)

The effect of exosomes derived from mesenchymal stem cells in the treatment of induced type 1 diabetes mellitus in rats - Dina Sabry; Samar Marzouk; Reem Zakaria; Heba A. Ibrahim; Mai Samir (Biotechnology Letters, 2020)

A novel genotype c.1228C>G/c.1448C-1498C (L371V/Rec-NciI) in a 3-year-old child with type 1 Gaucher disease - Nabil A. Yassin; Samar A. Muwakkit; Ahmad O. Ibrahim; Imad M. Kayim; Mohammad-Zohair M. Habbal; Nabil M. Chamseddine; Khaled M. Musallam; Ali I. Shamseddine (Journal of Applied Genetics, 2008)